Brucellosis Media Survey; Where Ohio Newspapers Get Agricultural News; A Media Survey Checklist - King F. Lovinger; G. P. Hettel; Gary R. Peterson (Journal of Applied Communications, 1981)
Three research briefs: Brucellosis Media Survey; Where Ohio Newspapers Get Agricultural News; A Media Survey ChecklistCattle brucellosis is a tough disease to conquer.